Megestrol Acetate Increases the Proliferation, Migration, and Adipogenic Differentiation of Adipose-Derived Stem Cells via Glucocorticoid Receptor. (13th May 2015) - Sung, Jong-Hyuk; An, Hyo-Sun; Jeong, Jin-Hyun; Shin, Soyoung; Song, Seung Yong
Abstract: : Because adipose-derived stem cells (ASCs) are usually expanded to acquire large numbers of cells for therapeutic applications, it is important to increase the production yield and regenerative potential during expansion. Therefore, a tremendous need exists for alternative ASC stimuli during cultivation to increase the proliferation and adipogenic differentiation of ASCs. The present study primarily investigated the involvement of megestrol acetate (MA), a progesterone analog, in the stimulation of ASCs, and identifies the target receptors underlying stimulation. Mitogenic and adipogenic effects of MA were investigated in vitro, and pharmacological inhibition and small interfering (si) RNA techniques were used to identify the molecular mechanisms involved in the MA-induced stimulation of ASCs. MA significantly increased the proliferation, migration, and adipogenic differentiation of ASCs in a dose-dependent manner. Glucocorticoid receptor (GR) is highly expressed compared with other nuclear receptors in ASCs, and this receptor is phosphorylated after MA treatment. MA also upregulated genes downstream of GR in ASCs, including ANGPTL4, DUSP1, ERRF11, FKBP5, GLUL, and TSC22D3 . RU486, a pharmacological inhibitor of GR, and transfection of siGR significantly attenuated MA-induced proliferation, migration, and adipogenic differentiation of ASCs. Although the adipogenic differentiation potential of MA was inferior to that of dexamethasone, MA had mitogenic effects in ASCs. Collectively, these results indicate that MA increases the proliferation, migration, and adipogenic differentiation of ASCs via GR phosphorylation. Significance: Magestrol acetate (MA) increases the proliferation, migration, and adipogenic differentiation of adipose-derived stem cells (ASCs) via glucocorticoid receptor phosphorylation. Therefore, MA can be applied to increase the production yield during expansion and can be used to facilitate adipogenic differentiation of ASCs. Abstract : The involvement of megestrol acetate (MA), a progesterone analog, in the stimulation of adipose-derived stem cells (ASCs) was investigated and the target receptors underlying stimulation were identified. The adipogenic differentiation potential of MA was inferior to dexamethasone, but MA had mitogenic effects in ASCs, indicating that MA increases the proliferation, migration, and adipogenic differentiation of ASCs via glucocorticoid receptor phosphorylation.